Meningkatkan Kemampuan Siswa Dalam Mengaplikasikan Rumus Fisika Dengan Menggunakan Metode Problem Solving Dalam Sintaks Pengajaran Langsung Pada Siswa Kelas VIIB SMP Muhammadiyah 1 Banjarmasin - Atqiya, Nurul; Jamal, Muhammad Arifuddin; Mahardika, Andi Ichsan (Berkala Ilmiah Pendidikan Fisika, 2016)
The studentsâs low ability in applying physics formula at class VII-B SMP Muhammadiyah 1 Banjarmasin will obstruct student in learning physics and give negative effect on learning outcome especially for material that includes formula. Therefore, this study was conducted to improve the studentsâs ability in applying physics formula by using problem solving method in direct instruction model at class VII-B SMP Muhammadiyah 1 Banjarmasin. This study utilized Hopkinâs model of classroom action research which consisted of 2 cycles, each cycle included plan, action/ observation, and reflection. The data were obtained from observation and test. The data were analyzed in descriptive qualitative and quantitative. The findings from first cycles to second cycles of this research were as follows: (1) The fidelity of lesson plans as a whole increased from 76,86% to 94,47%, (2) the studentâs skill procedure classicaly increased from 86,37% to 100%, (3) the studentsâs ability in applying physics formula increased from 59,09% to 95,94%, (4) the studentâs learning outcome classicaly increased from 59,09% to 95,94%. So, it can be concluded that problem solving method in direct instruction model can improve the studentsâs ability in applying physics formula in class VIIB SMP Muhammadiyah 1 Banjarmasin.